The lady in the tower - Jensen, Marie-Louise. (Oxford : Oxford University Press, 2009)
Spring 1540 I am afraid. You are in grave danger. Mother, will you run away with me if I can free you? The servants call it the Lady Tower: the isolated part of the castle where Eleanor's mother is imprisoned after a terrible accusation. For four years Eleanor's only comfort has been their secret notes to one another. A chance discovery reveals a plot to murder her mother. Now Eleanor must free her before it is too late. But with danger and betrayal at every turn, she can trust no one.Especially not her father. Eleanor must use all her cunning to survive. For she soon realises that it is not just her mother she needs to save . . . but also herself.
Keywords: Castle -- Fiction; Mothers and daughters -- Fiction